Wound healing and anti-inflammatory effects of Anethum graveolens extract loaded in PVA fibers: An in vitro and in vivo study. (July 2022) - Li, Linli; Wang, Fengjuan
Anethum graveolens extract (AGE) is known for its anti-inflammatory, antioxidative, and antibacterial activities. As wound infection, hyperactivity of inflammatory responses, and high oxidative stress are the leading causes of delayed wound healing, we were encouraged to design a delivery vehicle for AGE to develop a potential wound dressing material. In the current study, AGE was incorporated into the polyvinyl alcohol (PVA) scaffolds matrix via the electrospinning method. Various characterization methods were applied to assess the physicochemical and biological properties of the dressings. Cell culture studies with fibroblast cell line showed that AGE-loaded dressings could significantly promote cell viability under normal and oxidative stress conditions. The prepared wound dressings' wound healing and anti-inflammatory properties were investigated on an excisional injury rat model. Wound healing assay showed that AGE-delivering wound dressings could significantly improve the wound healing response, as evidenced by a significantly higher rate of wound closure, epithelial thickness, and collagen deposition. Gene expression analysis revealed that the produced dressings downregulated inflammation-associated genes such as IL-1β and NFK-β. This preliminary research suggests the potential applicability of AGE-loaded PVA dressings in the clinic.